The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

There's something in the water: Environmental racism in indigenous and black communities - Waldron, Ingrid (Fernwood Publishing, 2018)
Dans « Il y a quelque chose dans l'eau », Ingrid RG Waldron examine l'héritage du racisme environnemental et ses effets sur la santé dans les communautés autochtones et noires du Canada, en utilisant la Nouvelle-Écosse comme étude de cas, et les activités de résistance populaire des communautés autochtones et noires contre le la pollution et l'empoisonnement de leurs communautés. En utilisant le colonialisme des colons comme théorie globale, Waldron explique comment le racisme environnemental fonctionne comme un mécanisme d'effacement rendu possible par les dynamiques croisées de la suprématie blanche, du pouvoir, de la violence raciale sanctionnée par l'État, du néolibéralisme et du capitalisme racial dans les sociétés de colons blancs. Dans l'ensemble, le récit de la justice environnementale en Nouvelle-Écosse ne rend pas la race explicite, l'obscurcissant dans les discussions sur la classe, et ce type d'inadvertance stratégique atténue la spécificité des expériences des Mi'kmaq et des Afro-Néo-Écossais avec le racisme et les risques environnementaux en Nouvelle-Écosse. . En redéfinissant les paramètres de la critique autour du récit et du mouvement de justice environnementale en Nouvelle-Écosse et au Canada, Waldron ouvre un espace pour un dialogue plus critique sur la façon dont le racisme environnemental se manifeste dans ce contexte intersectionnel. Waldron illustre également la manière dont les effets du racisme environnemental sont aggravés par d'autres formes d'oppression pour déshumaniser et nuire davantage aux communautés déjà confrontées à des vulnérabilités préexistantes, telles que des inégalités sociales et économiques de longue date. Enfin, Waldron documente la longue histoire de lutte, de résistance et de mobilisation dans les communautés autochtones et noires pour lutter contre le racisme environnemental.
Keywords: amériques; approches et analyses; canada; cours; environnement; fem3600; militance; premier cycle; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques